A Standardized MRI Stroke Protocol - Peter D. Schellinger; Olav Jansen; Jochen B. Fiebach; Werner Hacke; K. Sartor (1999)
Background and Purpose —Diagnostic imaging in hyperacute ischemic stroke has been revolutionized by the introduction of diffusion- and perfusion-weighted MRI (DWI and PWI). CT, however, is still needed to exclude intracerebral hemorrhage (ICH). The purpose of our study was to determine the diagnostic accuracy of a standardized, multimodal MRI (mMRI) stroke protocol in the qualitative and quantitative assessment of hyperacute ICH (<6 hours). Methods —We investigated 9 patients with hyperacute ICH with CT followed immediately by a standardized mMRI stroke protocol (DWI, PWI [T2*-WI], FLAIR, T2-WI, and MRA). The time interval between MRI and symptom onset ranged from 3 hours to 5 hours 45 minutes. We analyzed and compared the size of the hematoma on CT and all mMRI images by semiautomatic volumetry. Results —ICH was unambiguously identified on the basis of all mMRI sequences. With increasing susceptibility effect (T2*-WI), the ICH, appearing as an area of hyperintensity with central signal loss, became qualitatively most evident. Regarding quantitation, T2*-WI overestimated (median and mean difference, 18.9%/17.8%; SD ς=24.4%) and DWI correlated best (median and mean difference, 3.97%/−4.36%; SD ς=37.42%) with hematoma size on CT. Conclusions —Multimodal stroke MRI is as reliable as CT in the assessment of hyperacute ICH. Therefore, additional CT is no longer necessary to rule out ICH in hyperacute stroke. The use of mMRI alone in the diagnostic workup of a hyperacute stroke patient saves time and costs while rendering all the critical information needed to initiate an optimal treatment.